All eight eyes. Volume 1 - Foxe, Steve (Dark Horse Books, 2023)
"In the forgotten corners of post-9/11 New York City, skittering shapes in the darkness prey on the people society leaves behind. College dropout Vin Spencer floats through life in a drug-and-party-fueled haze, until one terrible night sweeps him into a drifter's reckless war against the giant eight-legged horrors stalking the city."--